Joint attention communication and other minds : issues in philosophy and psychology - Eilan, Naomi (Oxford : Oxford University Press, 2005)
An international team of psychologists and philosophers present research into the cognitive phenomenon of 'joint attention'. Philosophical and psychological perspectives on the nature and significance of this phenomenon are examined.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Joint attention